2015
DOI: 10.1186/2055-5660-1-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a vaccine against Shigatoxin 2e in a piglet producing farm with problems of Oedema disease: case study

Abstract: Oedema disease is one of the major diseases in pigs during the nursery period. It is caused by Shigatoxin 2e producing strains of Escherichia coli. In order to combat the disease, the metaphylactic use of colistin sulphate and zinc oxide is widely spread. Additionally, special feeding regimens such as the reduction of the amount of crude protein and the increase of the amount of crude fibre are applied. The goal of this study was to test the efficacy of a vaccine against Oedema disease caused by Shigatoxin 2e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…Although a direct comparison between mortality (deaths plus runts) in this VG and mortality in a previous period, in which a combination of colistin and ZnO was used, could not be properly conducted because the groups may differ, it is interesting to highlight that mortality was virtually the same during the starter phase for both groups (0.14 vs. 0.15 1000 piglets-day at risk, respectively). The vaccine used in the present study, based on a genetically modified recombinant Stx2e, has already been shown to be apparently effective in reducing the use of colistin and the mortality rate (MR) during the nursery period [12,21]. Thus, this study supports previous results suggesting that vaccination against Stx2e may reduce mortality and may likely be used as an alternative to the use of colistin.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although a direct comparison between mortality (deaths plus runts) in this VG and mortality in a previous period, in which a combination of colistin and ZnO was used, could not be properly conducted because the groups may differ, it is interesting to highlight that mortality was virtually the same during the starter phase for both groups (0.14 vs. 0.15 1000 piglets-day at risk, respectively). The vaccine used in the present study, based on a genetically modified recombinant Stx2e, has already been shown to be apparently effective in reducing the use of colistin and the mortality rate (MR) during the nursery period [12,21]. Thus, this study supports previous results suggesting that vaccination against Stx2e may reduce mortality and may likely be used as an alternative to the use of colistin.…”
Section: Discussionsupporting
confidence: 88%
“…Edema disease caused by Stx2e-producing strains of E. coli can be a significant economic disorder in a pig production farm [12]. The cost of associated outbreaks depends on the mortality rate and weight of the pigs that die (the older the pigs, the more expensive the consequences).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, therapeutic options to treat human patients suffering from STEC-associated diseases are still limited at present and, if available [45], not directly counteracting the detrimental effects of the Stxs. Options to protect exposed human individuals against the development of Stx-induced diseases are not available [46] despite the fact that vaccination of piglets against Stx2e proved to be an effective strategy against ED in affected farms [47]. Preventive measures in place to mitigate the human health threat are implemented for the food chain (following the farm-to-fork concept) but are mainly limited to later stages of the chain (post-harvest food safety).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine edema disease (ED) primarily occurs in postweaned piglets and contributes to economic losses in swine industries worldwide (Fricke et al 2015). When the protection provided by maternal antibodies against F18 + Shiga toxin-producing Escherichia coli (STEC) during the weaning period disappears, the newly weaned piglets are highly susceptible to ED infection.…”
Section: Introductionmentioning
confidence: 99%